The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1248/cpb.c13-01005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Anti-proliferation Activities of Novel Cyano Oximino Sulfonate Esters

Abstract: A series of novel cyano oximino sulfonate derivatives were prepared from the reaction of arylsulfonyl chloride with different cyanoacetamide-based oximes ranging from the simplest unsubstituted amide to analogues containing N-ethyl (mimicking the Oxyma template), N-piperidinyl and N-morpholinyl chains. In addition, the cyano oximes, N-hydroxybenzimidoyl cyanide and N-hydroxypicolinimidoyl cyanide were also used in the synthesis of the novel cyano oximino sulfonate derivatives. The structures of the prepared co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Some oxime derivatives have been also examined as useful pharmacophores in a range of therapeutic agents and considered as bioisosteres which provide a series of potent antiviral agents [9][10][11][12][13]. Recently, O-acyl and O-arylsulfonyl derivatives of isatin 3-oximes have been synthesized and their reactivity towards alcohols and amines has been reported [14][15][16]. O-sulfonyl derivatives were reported with better reactivity than their analogous O-acyl derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Some oxime derivatives have been also examined as useful pharmacophores in a range of therapeutic agents and considered as bioisosteres which provide a series of potent antiviral agents [9][10][11][12][13]. Recently, O-acyl and O-arylsulfonyl derivatives of isatin 3-oximes have been synthesized and their reactivity towards alcohols and amines has been reported [14][15][16]. O-sulfonyl derivatives were reported with better reactivity than their analogous O-acyl derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…The two oximes 8 and 9 were synthesized according to the previously reported method 20 and used for the preparation of the sulfonate esters 11, 14 and 16. 20 2.2a General method for the synthesis of sulfonate esters: The reported method 20 was modified as follows:…”
Section: General Methods For the Synthesis Of Oxyma Derivativementioning
confidence: 99%
“…The analysis showed that these compounds (10)(11)(12)(13)(14)(15) have growth inhibition activity on L929 cells. 20 Herein, we report a modified method for the synthesis of the sulfonate esters using dichloromethanewater (two-phase method) in the presence of sodium carbonate for the scavenging of the HCl. X-ray crystallography was used to determine the structures of the three prepared sulfonate esters.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is one of the most important elements that constitute organisms and plays an important role in life activities of biomolecules. Cyano-oxime compounds and their derivatives have shown tremendous potentials for the development of a variety of biological compounds such as herbicides, drugs, and antibacterial agents (Gerasimchuk et al, 2008;El-Faham et al, 2014). The presence of two important functional groups in a single molecule makes them widely applicable for the synthesis of nitrogenous organic compounds in chemical engineering (Robertson et al, 2005;Aakeröy et al, 2012;Soliman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%